Eternal [compact disc, unabridged] - Scottoline, Lisa (Penguin Audio, 2021)
An aspiring writer, an athlete from a professional cyclist family and a mathematics prodigy find their bond tested by a love triangle and the spread of anti-Semitism and fascism in 1937 Italy.